The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15228070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetic Field and Temperature on Rheological Behavior of Magnetorheological Gel

Abstract: In this paper, the effect of temperature on rheological properties of magnetorheological (MR) gel is investigated under rotational steady shear and oscillatory dynamic shear. A kind of fluid-like MR gel (MRG) was firstly synthesized by mixing carbonyl iron powder (CIP) with polymer matrix. Then, the relationship between yield stress, normal stress of MRG and shear rate under six temperatures and four magnetic field strengths were studied by rotational shear experiments. The results demonstrate that the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Wang et al [ 11 ] investigated the relationship between the viscosity of base oils with different kinematic viscosities and the zero-field viscosity of lithium-based composite magnetorheological greases, and found that higher kinematic viscosity of the base oil leads to higher zero-field viscosity and improved sedimentation stability. In recent years, the use of clay minerals as additives [ 12 , 13 , 14 ] has been widely applied in magnetorheological materials, and sepiolite has gradually attracted the attention of scientists. Maurya et al [ 15 ] introduced goethite as an additive to water-based magnetorheological suspensions, resulting in the formation of a clay gel-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 11 ] investigated the relationship between the viscosity of base oils with different kinematic viscosities and the zero-field viscosity of lithium-based composite magnetorheological greases, and found that higher kinematic viscosity of the base oil leads to higher zero-field viscosity and improved sedimentation stability. In recent years, the use of clay minerals as additives [ 12 , 13 , 14 ] has been widely applied in magnetorheological materials, and sepiolite has gradually attracted the attention of scientists. Maurya et al [ 15 ] introduced goethite as an additive to water-based magnetorheological suspensions, resulting in the formation of a clay gel-like structure.…”
Section: Introductionmentioning
confidence: 99%